The portraits of an emperor: contributions to the historiographical debate on Nero and his Principate - Coelho, Ana Lucia Santos (Romanitas - Revista de Estudos Grecolatinos, 2019)
The purpose of this article is to demonstrate that, throughout history, Emperor Nero has undergone a process of abolition of memory, which helped to highlight his crimes and forge the monstrous image we have today. In this sense, we will examine how the most recognized contemporary scholars have resorted to such abolition to elaborate their own “Neros”.
Keywords: Ancient Rome; Neronian Principate; Negative literary tradition